The everything guide to calculus I a step-by-step guide to the basics of calculus-- in plain English! - Hill, Greg.; ebrary, Inc. (Avon, Mass. : Adams Media, 2011)
Calculus is the basis of all advanced science and math, but can be very intimidating. If finding derivatives or understanding integrals has you stumped, this guide offers hundreds of practice exercises and covers all the key concepts of calculus.
The top 10 ways to be successful in calculus -- Prerequisite skills -- Start building with limits -- The importance of continuity -- Getting differentiability straight -- Derivatives of polynomials -- Derivatives of trigonometric functions -- The chain rule -- Derivatives of other functions -- Derivatives of inverse trigonometric functions -- Higher-order derivatives -- Graph analysis using derivatives -- Applications of derivatives -- Area by numerical methods -- The definitive integral explored -- The fundamental theorem of calculus -- Methods of antidifferentiation -- Indefinite integrals -- The integral as an accumulator -- Applications of integrals.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Calculus; Electronic books